Moving to Mars: The Feasibility and Desirability of Mars Settlements - Puumala Mikko M.; Sivula Oskari; Lehto Kirsi (Elsevier Ltd, 2025)
The on-going space settlement debate has raised questions whether it is possible to settle other planets, and if it was, is it something humans should do. The problem with this space ethical discussion is that it can easily become too vague. To avoid this problem, we suggest a framework for identifying relevant variables that affect the feasibility constraints and desirability factors of establishing space settlements. The variables we focus on include the settlement stage, scale and time frame. Based on the relevant literature, we take mission cost, survival, habitation, water, in situ resources for food, oxygen and fuel energy and dependence on Earth as feasibility constraints that are relevant for the framework. None of them are hard constraints, but rather soft feasibility constraints that make it difficult to establish a permanent human settlement on Mars in the near- to medium-term future. However, in the past, humanity has achieved goals that first seemed infeasible. To justify the costs and effort, the goal must be highly morally desirable. We discuss five different desirability factors that could help justify the effort but as each framework has unique feasibility constraints, not all of these factors are sufficient or necessary to justify this effort. We argue that some of the desirability factors prominent in space ethical literature are not sufficient or necessary in our framework, and thus, we conclude that the normative grounds for establishing a permanent Mars settlement in the foreseeable future are weak.